Investigating some Factors Affecting the Milling of Long-Grain, High-Yielding Rice Varieties Dried in a Fluidized Bed Dryer - Mehdi Khodadadi; Mohammad Hashem Rahmati; Aminolah Masoumi (Biomechanism and Bioenergy Research, 2022)
In this study the effect of air temperature, paddy final moisture and variety on degree of whiteness and breakage percentage in fluidized bed dryer were investigated. Three rice varieties (Tarom-domsiah, Hashemi, and Shiroodi); air temperature in four levels (40, 45, 50 and 55°C) and final moisture in three levels (8-10, 10-12, and 12-14%) were considered. Tests were conducted within the factorial design. The results indicated that the degree of whiteness of Shiroodi variety is more than other varieties in different temperatures. Only the degree of whiteness of Tarom-domsiah is increased with increasing the moisture. The average degree of whiteness in moisture 8-10 percent was less than other moistures. Hashemi variety in each temperature indicated the least rice breakage percentage. Breakage percentage of Tarom-domsiah and Shiroodi varieties had no significant difference in any moisture levels. While Breakage percentage of Hashemi variety in 12-14% moisture had a significant difference in its breakage percentage in the moisture of 8-10% and 10-12% and it showed more breakage percentage value.